cis-acting sequences required for the germ line expression of the Drosophila gonadal gene. - Schulz, R.A.; Xie, X.L.; Miksch, J.L. (Developmental Biology, 1990)
We have identified two DNA sequences required for the proper germ line expression of the Drosophila gonadal (gdl) gene. A 53-bp region located from -328 to -276 relative to the gdlM transcription start site was required for the expression of a gdl-lacZ gene fusion in the male germ line. This sequence resides within the upstream z600 gene; however, z600 expression was undetectable in male germ cells. A 30-bp region located from -5 to +25 relative to the gdlF transcription start site was required for the expression of gdl-lacZ gene fusion in the female germ line.